Ear for recovery: protocol for a prospective study on parent–child communication and psychological recovery after paediatric injury. Issue 2 (4th February 2015) - Alisic, Eva; Barrett, Anna; Bowles, Peter; Babl, Franz E; Conroy, Rowena; McClure, Roderick J; Anderson, Vicki; Mehl, Matthias R
Abstract : Introduction: One in six children who have been admitted to hospital with an injury develop persistent stress symptoms that put their development at risk. Parents play a crucial role in children's psychological recovery, however, it is unknown how specific parenting behaviours can help or hinder. We aim to describe the nature and quantity of parent–child communication after a child has been injured, and to examine how these interactions are related to children's psychological recovery. Methods and analysis: We are conducting a prospective observational study among children aged 3–16 years, who have been admitted to a tertiary children's hospital with a serious injury. Data collection involves a naturalistic observation of spontaneous, everyday parent–child communication at home, shortly after discharge, and an assessment of children's psychological recovery at 6 weeks and 3 months post-injury. Main analyses comprise descriptive statistics, cluster analysis and analyses of variance. Ethics and dissemination: This study has been approved by the Human Research Ethics Committee of the Royal Children's Hospital Melbourne (33103) and Monash University Human Research Ethics Committee (CF13/2515—2013001322). We aim to disseminate the findings through international peer-reviewed journals, international conferences and social media. Participants will be sent a summary of the overall study findings.